Mitochondrial biogenesis by NO yields functionally active mitochondria in mammals - Nisoli, Enzo (National Academy of Sciences, 2004)
We recently found that long-term exposure to nitric oxide (NO) triggers mitochondrial biogenesis in mammalian cells and tissues by activation of guanylate cyclase and generation of cGMP. Here, we report that the NO/cGMP-dependent mitochondrial biogenesis is associated with enhanced coupled respiration and content of ATP in U937, L6, and PC12 cells. The observed increase in ATP content depended entirely on oxidative phosphorylation, because ATP formation by glycolysis was unchanged. Brain, kidney, liver, heart, and gastrocnemius muscle from endothelial NO synthase null mutant mice displayed markedly reduced mitochondrial content associated with significantly lower oxygen consumption and ATP content. In these tissues, ultrastructural analyses revealed significantly smaller mitochondria. Furthermore, a significant reduction in the number of mitochondria was observed in the subsarcolemmal region of the gastrocnemius muscle. We conclude that NO/cGMP stimulates mitochondrial biogenesis, both in vitro and in vivo, and that this stimulation is associated with increased mitochondrial function, resulting in enhanced formation of ATP.